Incidence of fentanyl induced cough and fentanyl induced cough as a risk factor for post operative nausea and vomiting - Sis Jose,; Apoorwa Nawrathan Kothari,; Rashmi Rani,; Usha Ramakrishna Sastry,; Deepa Baskaran,; Arpana Kedlaya, (Asian Journal of Medical Sciences, 2024)
Background: Fentanyl-induced cough (FIC) is an undesirable side effect associated with intravenous injection of the opioid fentanyl, which can lead to an increase in intraocular, intrathoracic, and intraabdominal pressures. The incidence of FIC is reported to be 18–65%, more common in young females, who are also at high risk population for post-operative nausea and vomiting (PONV). FIC and PONV are both common anesthesia-related events that seem to have common risk factors. Aims and Objectives: The objectives of the study were to find out the incidence of FIC in female patients undergoing elective surgery under general anesthesia and if FIC was a risk factor for developing PONV. Materials and Methods: A randomized, prospective study was done to compare the incidence of FIC and its correlation with PONV. 263 adult female patients belonging to American Society of Anesthesiologists status I and II, aged 18–59 years, posted for elective surgery under general anesthesia were studied over a period of 2 years. Pre-operatively, fentanyl (2 mg/kg body weight) was injected intravenously over 10 s as premedication, and the occurrence of any episode of cough within 60 s of fentanyl administration was taken as FIC. The incidence and severity of PONV were assessed in the same study population for a 24-h period. The incidence of FIC during general anesthesia in the study population was noted, and its correlation with PONV was analyzed. Results: The incidence of FIC in the study population was found to be 27%. The incidence of PONV in the FIC group was found to be 38%, as compared to 29.7% in the non-FIC group. FIC group had a higher incidence of PONV than the non-FIC group, but it was statistically insignificant (P=0.254). Conclusion: The incidence of PONV was slightly higher in the FIC group than in the non-FIC group, but it was not statistically significant.